Practical use of musculoskeletal ultrasonography in rheumatoid arthritis: how to use this attractive but arduous tool in clinical practice. (December 2015) - Ohno, Shigeru
Musculoskeletal ultrasonography (MSUS) is now commonly used by many rheumatologists in clinical practice, but much work is still required for its optimization. MSUS use in daily clinical practice should be feasible and practicable, at the same time, not redundant. MSUS should be used as a complementary procedure and not as an alternative to systematic clinical evaluation. MSUS can be minimally used on demand, at the point of care, to detect subclinical synovitis. Grading and scoring by ultrasonography in addition to clinical examination are not always required for the regular management of individual patient.